Organizational and economic conditions for ensuring the quality of arrangement and provision of sports services (the case of sports events) - E. A. Mozhelev (Путеводитель предпринимателя)
The author of the article specifies the essence of the concept «organizational and economic conditions for ensuring the quality of arrangement and provision of sports services» and what is more, identifies and describes the main types of organizational and economic conditions for ensuring the quality of sports services at the macro level (at country level) and micro level (at the level of certain organizations), with reference to which the system of organizational and economic conditions for ensuring the quality of arrangement and provision of sports services (the case of sports events) is developed.